How Green Practice Can Drive Green Loyalty Of Slow Fashion Consumers? - Mahmud, Adinda Amalia; Balqiah, Tengku Ezni (Sekolah Tinggi Manajemen IPMI, 2025)
This research aims to analyze the influence green image and green practice towards product loyalty slow fashion with green trust, green perceived value and green satisfaction as mediating variables brand slow fashion in Indonesia, this research used a quantitative descriptive method with 239 respondents who were product buyers slow fashion in the last 6 months, data was processed using the SmartPLS version 3 application to answer fifteen hypotheses in this research, the results of the study found a positive influence from green practice to green image, green loyalty, green trust, green perceived value and green satisfaction, while research finds that green image has no effect on green trust and green satisfaction, This research succeeded in generating a new paradigm regarding consumer loyalty in using environmentally friendly products and how environmentally friendly practices in the fashion industry can support environmentally friendly efforts. This research provides an overview of environmentally friendly practices in non-service companies.